The influence of PBL on students' scientific literacy in ecosystem material for grade X - Meliya Salsabilla; Kartika Manalu (Inovasi Kurikulum, 2025)
This study stemmed from a concern over low student scientific literacy, reflected explicitly in the gap between theoretical concept mastery and the inability to apply this knowledge to analyze real and complex local ecological problems. Its primary objective was to analyze the significant impact of the Problem-Based Learning (PBL) model on developing students' scientific literacy regarding ecosystem components and interactions. Using a quasi-experimental approach, the research compared a group of students receiving instruction based on authentic problems against a control group following conventional teaching methods. Data were collected via pre-test and post-test instruments designed to measure various dimensions of scientific literacy. The results indicated a striking and statistically significant difference in achievement. The experimental group demonstrated an exceptional leap in understanding, with nearly all students successfully reaching the highest category of scientific literacy. In contrast, the control group showed only limited improvement, with the majority of students remaining at a moderate level of understanding. This finding conclusively proves that PBL is superior in transforming passive instruction into an active learning experience, training students to think critically, construct scientific arguments, and apply biological knowledge in a relevant and meaningful way.   Abstrak Penelitian ini berangkat dari keprihatinan atas rendahnya literasi sains peserta didik, yang secara spesifik tecermin dari kesenjangan antara penguasaan konsep teoretis dan ketidakmampuan untuk menerapkan pengetahuan tersebut dalam menganalisis masalah ekologis lokal yang nyata dan kompleks. Tujuan utamanya adalah untuk menganalisis pengaruh signifikan dari model Problem-Based Learning (PBL) terhadap pengembangan literasi sains peserta didik pada materi komponen dan interaksi ekosistem. Menggunakan pendekatan kuasi-eksperimen, penelitian ini membandingkan kelompok peserta didik yang menerima pembelajaran berbasis masalah autentik dengan kelompok kontrol yang mengikuti metode pembelajaran konvensional. Data dikumpulkan melalui instrumen pretest dan posttest yang dirancang untuk mengukur berbagai dimensi literasi sains. Hasilnya menunjukkan sebuah perbedaan capaian yang sangat mencolok dan signifikan secara statistik. Kelompok eksperimen menunjukkan lonjakan pemahaman yang luar biasa, di mana hampir seluruh peserta didik mampu mencapai kategori literasi sains tertinggi. Sebaliknya, kelompok kontrol hanya menunjukkan peningkatan yang terbatas, dengan mayoritas peserta didik tertahan pada tingkat pemahaman sedang. Temuan ini secara konklusif membuktikan bahwa PBL secara superior mampu mentransformasi pembelajaran pasif menjadi pengalaman belajar aktif, melatih peserta didik berpikir kritis, berargumentasi ilmiah, dan mengaplikasikan pengetahuan biologi secara relevan dan bermakna. Kata Kunci: komponen ekosistem; literasi sains; PBL; pembelajaran berbasis masalah